Use of Biometric Data on Crypto Platforms in the Perspective of Islamic Economics - Dea Amanda Wulandari; Sukron Makmun; Kisanda Midisen; Sakum; MH Ainulyaqin (LP2M IAIN Palopo, 2026)
Advances in digital technology, particularly in blockchain-based financial systems, have driven the increasingly widespread use of cryptocurrency in society. As the use of crypto platforms grows, security has become a primary concern, leading many platforms to adopt biometric authentication technologies such as fingerprint and facial recognition. This study aims to analyze the use of biometric data on crypto platforms and assess its suitability from an Islamic economic perspective. From an Islamic economic perspective, the use of biometric data on crypto platforms is fundamentally permissible because it does not involve elements of gharar, maysir, or riba; however, its use must adhere to the principle of benefit, protect privacy, and not cause harm to users. Thus, biometric technology is acceptable within the Islamic economy provided it is managed securely, transparently, and in accordance with Sharia principles.